The Effect of Problem Centered Learning (PCL) Approach to Critical Thinking Skills of Class XI MAS Tanah Datar District - Muhammad Hafiz; Ali Asmar; Yerizon Yerizon (Jurnal Pendidikan Matematika RAFA, 2020)
The mathematics learning outcomes of MAS students in Tanah Datar Regency are still relatively low. This is because students who enter private schools are students who do not pass the selection in public schools, besides learning is still centered on the teacher and the lack of critical thinking skills of students is one of the obstacles that affect the low student learning outcomes. One of the efforts is made to overcome this problem is to apply the PCL approach to learning. This study aims to determine the effect of the PCL approach on students' critical thinking skills, especially in line and series material. The study was conducted on two classes which were used as the experimental class and the control class. In the experimental class the treatment of learning was given by applying the PCL approach while the control class was given treatment with conventional learning. The research data was obtained from the results of the initial ability test (pre-test) given before the sequences and series subject matter was started and the final test (post-test) was given after the PCL treatment was carried out, while the data analysis was performed using non-parametric tests because the data was not normally distributed and has a non-homogeneous variance. The results of data analysis showed that there was the influence of the PCL approach to critical thinking skills of students class XI of MAS Salimpaung. The critical thinking of students with PCL approach was better than the critical thinking of students taught with conventional learning in class XI MAS Salimpaung.